Prescribing Analgesics to Older People: A Challenge for GPs - Majnarić, Ljiljana Trtica (Int J Environ Res Public Health, 2020)
Background: Due to population aging, there is an increase in the prevalence of chronic diseases, and in particular musculoskeletal diseases. These trends are associated with an increased demand for prescription analgesics and an increased risk of polypharmacy and adverse medication reactions, which constitutes a challenge, especially for general practitioners (GPs), as the providers who are most responsible for the prescription policy. Objectives: To identify patterns of analgesics prescription for older people in the study area and explore associations between a long-term analgesic prescription and comorbidity patterns, as well as the prescription of psychotropic and other common medications in a continuous use. Methods: A retrospective study was conducted in 2015 in eastern Croatia. Patients were GP attenders ≥40 years old (N = 675), who were recruited during their appointments (consecutive patients). They were divided into two groups: those who have been continuously prescribed analgesics (N = 432) and those who have not (N = 243). Data from electronic health records were used to provide information about diagnoses of musculoskeletal and other chronic diseases, as well as prescription rates for analgesics and other medications. Exploratory methods and logistic regression models were used to analyse the data. Results: Analgesics have been continuously prescribed to 64% of the patients, mostly to those in the older age groups (50–79 years) and females, and they were indicated mainly for dorsalgia symptoms and arthrosis. Non-opioid analgesics were most common, with an increasing tendency to prescribe opioid analgesics to older patient groups aged 60–79 years. The study results indicate that there is a high rate of simultaneous prescription of analgesics and psychotropic medications, despite the intention of GPs to avoid prescribing psychotropic medications to patients who use any option with opioid analgesics. In general, receiving prescription analgesics does not exceed the prescription for chronic diseases over the rates that can be found in patients who do not receive prescription analgesics. Conclusion: Based on the analysis of comorbidities and parallel prescribing, the results of this study can improve GPs’ prescription and treatment strategies for musculoskeletal diseases and chronic pain conditions.